PENGUKURURAN KESEHATAN MENTAL KARYAWAN DENGAN DASS-21 PADA DEPERTEMEN K3&LH DI PT XYZ - Athaya Naomi Nabilah; Fahriza Nurul Azizah; Alinda Febianti; Fitri Nuraliza (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Employee mental health is a crucial factor influencing productivity and workplace safety in industrial environments. Problems such as stress, anxiety, and depression can arise due to high workloads, significant responsibilities, and the potential risk of accidents inherent in work activities. This study aims to measure the mental health of employees in the Occupational Health and Safety Department at PT XYZ using the Depression Anxiety Stress Scales (DASS-21) and analyze its implications for work productivity. The research method used was descriptive quantitative with a cross-sectional design. Data were obtained by distributing the DASS-21 questionnaire to 13 respondents, then the results were classified into five severity categories: normal, mild, moderate, severe, and very severe. The results showed that most respondents were in the normal to moderate category, although there were individuals with relatively high levels of anxiety and stress. These findings indicate that in general, employee mental health is still in a reasonable condition, but special attention is still needed for individuals at risk. The conclusion of this study is that the mental health condition of employees of the K3&LH Department of PT XYZ is generally at a normal to moderate level, but special attention is still needed for individuals who show symptoms of stress and anxiety so that productivity and work well-being can be maintained optimally. Keywords: Mental health,Work productivity, K3&LH, DASS-21